2003
DOI: 10.1001/archinte.163.17.2058
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Association With Severe Obesity

Abstract: Severely obese subjects, especially younger women with poor body image, are at high risk for depression. We found sustained improvement with weight loss. These findings also support the hypothesis that severe obesity causes or aggravates depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
269
2
38

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(332 citation statements)
references
References 52 publications
23
269
2
38
Order By: Relevance
“…It has been pointed out that depression should be considered another comorbidity of obesity. 38 In the present study, high rates of depression cases were observed in both treatment groups before treatment. The estimated The SOS study: 10-year follow-up of quality of life J Karlsson et al prevalence according to the HAD depression scale was 2.7 and 4 times higher, respectively, in the conventional and surgical group than in the nonobese reference population.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It has been pointed out that depression should be considered another comorbidity of obesity. 38 In the present study, high rates of depression cases were observed in both treatment groups before treatment. The estimated The SOS study: 10-year follow-up of quality of life J Karlsson et al prevalence according to the HAD depression scale was 2.7 and 4 times higher, respectively, in the conventional and surgical group than in the nonobese reference population.…”
Section: Discussionsupporting
confidence: 51%
“…In a prospective study, Beck Depression Inventory (BDI) was used to assess symptoms of depression in patients at yearly intervals up to 4 years after gastric banding. 38 High scores before treatment decreased with about one-half during the first year postsurgically and most of the positive effect remained in patients available for follow-up after 4 years; however, mean scores tended to increase between 1 and 4 years. In line with the present study, greater weight loss was associated with greater reduction of depression symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…Additional support for a causal pathway from obesity to psychiatric disturbance, most notably depression, comes from research on change in psychopathologic features among obese individuals as a function of weight loss after behavioral, dietary 18,19 or surgical 20,21 intervention. For example, Dixon et al 20 reported a significant and sustained drop in scores on the Beck Depression Inventory from 17.779.5 at baseline to 7.876.5 and 9.677.7 1 and 4 years later, respectively, following gastric-restrictive weight loss surgery. Nonetheless, obese individuals who enter weight reduction programs are reported to be more depressed or more anxious than obese individuals in the general population, and thus may be more likely to experience a decline in symptoms with weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…A obesidade é a doença física mais comum e crônica na sociedade moderna e a depressão é a condição psicológica mais prevalente. Embora haja alta prevalência para essas duas condições, a exploração de qualquer associação entre elas tem sido limitada 6 .…”
Section: N T R O D U ç ã Ounclassified